The Defence Makeover : 10 Myths that Shape India's Image - Sawhney, Pravin (New Delhi Sage Publications, 2002)
This unusual and timely book examines ten questions that are most frequently asked and debated in the context of India's national security. Referring to each of these questions as "myths", the author, once a serving officer in the Indian army, proceeds to systematically shatter them, thus challenging conventional wisdom.
Includes Maps and Illustrations.
Keywords: India -- China -- Pakistan